MELAYU ISLAM BERAJA FONDASI KUAT SISTEM HUKUM DAN PERADILAN BRUNEI DARUSSALAM - Aulia Islami, Dina; Asasriwarni; Zulfan (Prodi Hukum Keluarga Islam IAI Uluwiyah Mojokerto, 2026)
Brunei Darussalam is an absolute monarchy with the Malay Islamic Monarchy (MIB) philosophy that combines Malay culture, Islamic teachings, and the sultanate system in its legal and governmental structure. Brunei's legal system is dual in character: common law inherited from the British Empire and Islamic law, which was further strengthened after independence in 1984. This dynamic reached a critical point with the enactment of the Sharia Penal Code Order (SPCO) 2013, which expanded the scope of Islamic law from the family sphere to the criminal sphere. This article aims to analyze the development of Brunei's legal and judicial system within the MIB framework and examine legal reforms through the SPCO 2013. The research method used is a qualitative literature study approach, through a review of primary literature in the form of regulations and official documents, as well as secondary literature such as journal articles, books, and academic publications. The results of the study indicate that Brunei's legal system was formed from the interaction between British colonial influences, Islamic traditions, and the political legitimacy of the Sultan, united by the MIB ideology as a normative basis. The 2013 SPCO emphasized a more comprehensive transformation of Islamic law, despite international criticism regarding hudud punishments. In conclusion, Brunei's legal system serves not only as a normative tool but also as a political, social, and cultural instrument in strengthening the nation's identity.